The impact of base design and restoration type on the resin consumption, trueness, and dimensional stability of dental casts additively manufactured from liquid crystal display 3D printers - Tseng, Chih‐Wei; Lin, Wei‐Shao; Sahrir, Citra Dewi; Lin, Wei‐Chun (Journal of prosthodontics, 2025)
Purpose To evaluate the effects of two base types and three restoration designs on the resin consumption and trueness of the 3D‐printed dental casts. Additionally, the study explored the dimensional stability of these 3D‐printed dental casts after 1 year of storage. Materials and Methods Various types of reference dental casts were specifically designed to represent three types of dental restoration fabrications, including full‐arch (FA), long‐span (LS), and single‐unit (SU) prostheses. The reference casts were digitized with a dental laboratory scanner and used to create flat and hollow base designs (N = 18) for the 3D‐printed study casts. The 3D‐printed study casts were digitized and evaluated against their corresponding references immediately after 3D printing and again after 1 year of storage, with the trueness quantified using the root mean square error (RMSE) at both time points. Volumes of resin used were recorded to measure resin consumption, and the weights of the 3D‐printed study casts were also measured. The data were analyzed using two‐way ANOVA and a Tukey post hoc test, α = 0.05. Results Volumetric analysis showed the flat‐base design had significantly higher resin consumption with weights for the FA group at 42.51 ± 0.16 g, the LS group at 31.64 ± 0.07 g, and the SU group at 27.67 ± 0.31 g, as opposed to 26.22 ± 1.01 g, 22.86 ± 0.93 g, and 20.10 ± 0.19 g for the hollow designs respectively (p < 0.001). Trueness, assessed through two‐way ANOVA, revealed that the flat‐base design had lower RMSE values indicating better trueness in the LS (54 ± 6 µm) and SU (59 ± 7 µm) groups compared to the hollow‐base design (LS: 73 ± 5, SU: 99 ± 11 µm, both p < 0.001), with no significant difference in the FA group (flat‐base: 50 ± 3, hollow: 47 ± 5 µm, p = 0.398). After 1 year, the flat‐base design demonstrated superior dimensional stability in the LS (flat base: 56 ± 6 µm, hollow base: 149 ±45 µm, p < 0.001) and SU groups (flat base: 95 ± 8 µm, hollow base: 183 ±27 µm, p < 0.001), with the FA group showing no significant difference in the base design (flat base: 47 ± 9, hollow base: 62 ± 12 µm, p = 0.428). Conclusions The hollow‐base design group showed lower resin consumption than the flat‐base design group. However, the flat‐base designs exhibited superior trueness and less distortion after 1 year of storage. These findings indicate that despite the higher material usage, flat‐base designs provide better initial accuracy and maintain their dimensional stability over time for most groups.